Pharmacological potential of Withania somnifera (L.) Dunal and Tinospora cordifolia (Willd.) Miers on the experimental models of COVID-19, T cell differentiation, and neutrophil functions - Rizvi, Zaigham Abbas; Babele, Prabhakar; Madan, Upasna; Sadhu, Srikanth; Tripathy, Manas Ranjan; Goswami, Sandeep; Mani, Shailendra; Dikshit, Madhu; Awasthi, Amit (Frontiers in Immunology, 2023)
Severe acute respiratory coronavirus-2 (SARS-CoV-2) infection results in pulmonary pathology characterized by cytokine release syndromes (CRS) leading to cellular injury. Moreover, a severe form of coronavirus disease (COVID-19) is mostly presented with pneumonitis and respiratory distress leading to mortality. The available options for the clinical management of COVID-19 are anti-viral and immunomodulatory drugs, while the major limitation of the available drugs is their off-target effects. Centuries-old Asian traditional medicines such as Withania somnifera (WS) and Tinospora cordifolia (TC) possess potent immune-modulatory effects. In the present study, we tested the efficacy of WS and TC in the hamster model of SARS-CoV-2 infection at the human equivalent doses. While both WS and TC showed immuno-modulatory potential, only hamsters receiving WS showed robust protection against loss in body weight, viral load, and pulmonary pathology associated with the suppression of pro-inflammatory cytokines and Th1, Th2, and Th17 differentiation. In addition, WS treatment inhibited ROS generation from neutrophil under in-vitro condition. We further used hACE2 transgenic mice representing acute infection to investigate detailed mechanisms of WS-induced protection SARS-CoV2 infection. Prophylactic treatment of WS in hACE2 mice showed a significant protection against body weight loss and a decrease in lung viral load. Further, flow cytometry data suggested that WS boosted the immune-suppressive environment which seems to limit the worsening of the disease due to inflammation. Together, we provide pre-clinical data from mild and severe infection models suggesting robust protection by WS against COVID-19 through its broader immunomodulatory activity. Our study supports the evaluation of WS alone or as a formulation for therapeutic intervention against acute viral infections.